2015
DOI: 10.5021/ad.2015.27.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Skin Explants for Histologic Analysis after Fractional Photothermolysis

Abstract: BackgroundFractional laser resurfacing treatment has been extensively investigated and is widely used. However, the mechanism underlying its effects is poorly understood because of the ethical and cosmetic problems of obtaining skin biopsies required to study the changes after laser treatment.ObjectiveTo evaluate the usefulness of human skin explants for the investigation of fractional photothermolysis.MethodsFull-thickness discarded skin was treated in 4 ways: no treatment (control), fractional carbon dioxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Cytokine stimulation of HESC provoked immune cell responses with release of chemokines, antimicrobial peptides and keratinocyte differentiation markers associated with clinical psoriasis 10 . However, in the HESC model literature 1 , 6 , 11 13 , a general increase in epidermal thickness is noted over the first week in culture with a decrease in tissue integrity and keratinocyte differentiation occurring after ~ 14 days. In addition, a loss of keratinocyte proliferation is accompanied by an increase in keratinocyte apoptosis evident after the first week 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine stimulation of HESC provoked immune cell responses with release of chemokines, antimicrobial peptides and keratinocyte differentiation markers associated with clinical psoriasis 10 . However, in the HESC model literature 1 , 6 , 11 13 , a general increase in epidermal thickness is noted over the first week in culture with a decrease in tissue integrity and keratinocyte differentiation occurring after ~ 14 days. In addition, a loss of keratinocyte proliferation is accompanied by an increase in keratinocyte apoptosis evident after the first week 9 .…”
Section: Introductionmentioning
confidence: 99%
“…1f, g) and poor reproducibility beyond 21 days partly due to coiling up of the explant, which enclosed the exposed surface (data not shown). However, human dermal explants cultured at a liquid–air interface in vitro have been shown by others to remain viable after 7 days [12] and in some cases 75 days [11]. While no keratinocytes were detected on explant surfaces after 7 days (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…1i, l). This varied keratinocyte distribution may be due to differences in the physical features of the two dermal layers, though others have demonstrated variation in ECM biochemistry, including that which affects keratinocyte proliferation and migration (i.e., hyaluronan and other proteins) as well as ECM remodelling, across dermal layers [11].…”
Section: Resultsmentioning
confidence: 99%
“…The difference may be linked to the lower concentration of calcium ions in the culture medium. While we and Frade et al () used media with a high concentration of calcium (~1.35 and 1.8 mmol/L, respectively), Park et al () used RPMI 1640 medium with 0.4 mmol/L of calcium. This phenomenon was earlier described by Varani et al .…”
Section: Discussionmentioning
confidence: 93%
“…This agrees with previous reports by Frade et al () and Balaji et al (). On the other hand, Park et al showed detachment of the spinous layer in the epidermis and degenerative changes in dermal collagen after 7 days of HSE in culture Park et al (). The difference may be linked to the lower concentration of calcium ions in the culture medium.…”
Section: Discussionmentioning
confidence: 99%